Human animality and realistic naturalism in Alasdair MacIntyre - Sousa, José Elielton de (2024)
Neo-Aristotelian philosopher, Alasdair MacIntyre, proposes, in Dependent Rational Animals (1999), a naturalistic virtue ethics, anchored in the animal identity of human beings, together with the vulnerability and dependence to which we are subjected, as biologically constituted animals. He recognizes that, by using the term “good” as a direct reference to the flourishing of members of some animal or plant species as members of those species, he is offering a naturalistic interpretation of the good, but he does not make clear what kind of naturalism he is committed to, not providing further explanations about what is understood by natural good and not presenting details about how to resolve this issue of the relationship between the good and its natural properties. So, we must ask what kind of naturalism does MacIntyre endorse. Does his naturalism meet the minimum requirements of an updated neo-Aristotelian naturalist proposal? These are some of the questions that we will analyze throughout this text.